Psychometric Properties of the Checklist of Experiences of Psychological Abuse to the Couple in Adolescents and Young Adults - Rey Anacona, César Armando (Journal of interpersonal violence, 2021)
In Ibero-America, interest in the evaluation and prevention of violence in young couples has been increasing. However, there are not enough Spanish-speaking standardized questionnaires. The psychometric analyses of the Checklist of Experiences of Psychological Abuse to the Couple (CEPA) are presented as a subset of the Checklist of Experiences of Abuse to the Couple. Overall, 1,505 adolescents participated; 828 were women, and 677 were men, aged 14 to 21 years old. A confirmatory factor analysis with the Structural Equation Modeling Software version 6.2 (EQS) was performed to consider different factor models that were consistent with theoretical and empirical aspects about violence in young couples. A structure was obtained with one factor of higher order, “Psychological Aggression” (14 items), and the following three primary factors: (a) “Coercion” (four items), (b) “Humiliation” (five items), and (c) “Control” (five items); Cronbach’s alpha ranged from .71 to .83. The overall scale and the three subscales correlated significantly with each other and with negative personality traits associated with gender. The results indicate that the scale has adequate psychometric properties for use in clinical practice and research.